Remote activation of nanoparticulate biomimetic activity by light triggered pH-jump12. Issue 62 (18th July 2018) - Wang, Xiaopei; Gong, Ao; Luo, Wenhao; Wang, Haiqing; Lin, Changxu; Liu, Xiang Yang; Lin, Youhui
Abstract : By incorporating flash photolysis reagents, a facile and versatile method for the photo-regulation of pH-dependent activities of artificial enzymes is presented. Abstract : Herein, we report a facile, efficient and versatile method for the photo-regulation of pH-dependent activities of artificial enzymes by incorporating flash photolysis reagents. Under light excitation, a persistent pH shift is achieved by proton release from photosensitive 2-nitrobenzaldehyde. Following such change, the controlled activation of oxidase-like activity of nanoceria is successfully demonstrated.